Staphylococcus carnosus: from starter culture to protein engineering platform - Löfblom, John (Appl Microbiol Biotechnol, 2017)
Since the 1950s, Staphylococcus carnosus is used as a starter culture for sausage fermentation where it contributes to food safety, flavor, and a controlled fermentation process. The long experience with S. carnosus has shown that it is a harmless and “food grade” species. This was confirmed by the genome sequence of S. carnosus TM300 that lacks genes involved in pathogenicity. Since the development of a cloning system in TM300, numerous genes have been cloned, expressed, and characterized and in particular, virulence genes that could be functionally validated in this non-pathogenic strain. A secretion system was developed for production and secretion of industrially important proteins and later modified to also enable display of heterologous proteins on the surface. The display system has been employed for various purposes, such as development of live bacterial delivery vehicles as well as microbial biocatalysts or bioadsorbents for potential environmental or biosensor applications. Recently, this surface display system has been utilized for display of peptide and protein libraries for profiling of protease substrates and for generation of various affinity proteins, e.g., Affibody molecules and scFv antibodies. In addition, by display of fragmented antigen-encoding genes, the surface expression system has been successfully used for epitope mapping of antibodies. Reviews on specific applications of S. carnosus have been published earlier, but here we provide a more extensive overview, covering a broad range of areas from food fermentation to sophisticated methods for protein-based drug discovery, which are all based on S. carnosus.